Ethical Issues When Considering Liver Donor Versus Deceased Donor Liver Transplantation. Issue 2 (28th February 2021) - Nizamuddin, Imran; Gordon, Elisa J.; Levitsky, Josh
Abstract : Watch a video presentation of this article